2014
DOI: 10.1121/1.4881919
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic streaming of a sharp edge

Abstract: Anomalous acoustic streaming is observed emanating from sharp edges of solid bodies that are vibrating in fluids. The streaming velocities can be orders of magnitude higher than expected from the Rayleigh streaming at similar amplitudes of vibration. Acoustic velocity of fluid relative to a solid body diverges at a sharp edge, giving rise to a localized time-independent body force acting on the fluid. This force results in a formation of a localized jet. Two-dimensional numerical simulations are performed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 17 publications
10
115
0
1
Order By: Relevance
“…The results shown in this study can be envisioned in a larger scope, including in applications of mixing and homogenization of fluids, which requires the generation of flow at a large distance from the source. Very recent studies focused on situations of a more complex geometry [39], microfluidics [22,23,46] or nonlinear interactions between streaming and acoustic waves in acoustic streaming [47]. Depending on the size ratio between the mechanical actuator (or the acoustic wavelength) and the vessel, operating in conditions of high-Reynolds number flows can generate a flow whose spatial extension can be as large as the vessel or channel size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shown in this study can be envisioned in a larger scope, including in applications of mixing and homogenization of fluids, which requires the generation of flow at a large distance from the source. Very recent studies focused on situations of a more complex geometry [39], microfluidics [22,23,46] or nonlinear interactions between streaming and acoustic waves in acoustic streaming [47]. Depending on the size ratio between the mechanical actuator (or the acoustic wavelength) and the vessel, operating in conditions of high-Reynolds number flows can generate a flow whose spatial extension can be as large as the vessel or channel size.…”
Section: Resultsmentioning
confidence: 99%
“…Incidentally, it is remarkable that the streaming flow is related to the non-zero local curvature of the vibrating object. This is reminiscent of the streaming induced by acoustic fields in microchannels either around cylindrical or squared posts [21], or near sharp edges [22,23,24] which concentrate the streaming force.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on the acoustic streaming around oscillating sharp edge geometries have been published for frequencies of 461 Hz (Ovchinnikov et al 2014) and 4.75 kHz , also in combination with acoustic radiation forces. The results of these studies show that the complex streaming pattern depends on boundary conditions ) as the geometry, the direction of vibration of the sharp edge, and the radius of curvature at the tip of the sharp edge, while the driving mechanism of the streaming is the rushing of the fluid from one side of the sharp edge to the other (Ovchinnikov et al 2014). We implemented an analog numerical approach in Comsol Multiphysics to obtain an exemplary streaming pattern in Fig.…”
Section: Numerical Modelingmentioning
confidence: 98%
“…In the previous study, 27 we considered a periodic cell of the sharp-edge-based micromixer and investigated the flow patterns to predict the effect of various geometrical and operational parameters on the performance of the sharp-edge-based micromixer. Another numerical study of the flow patterns around a single sharp-edge and their scaling has been reported recently by Ovchinnikov et al 28 More recently, the sharp-edge-based mixing platform has been utilized for other biomedical applications such as a chemical gradient generator, 29 and liquefaction of high viscosity samples such as human sputum. 30 While promising applications of the sharp-edge platform have been demonstrated experimentally including particle trapping by acoustic radiation forces, 31 the numerical studies reported so far have focused only on the investigation of the flow field around the sharp-edges in the absence of a background flow, without any modeling of the mixing phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Second, we allow for a non-zero background laminar flow to consider a more realistic case of the interaction of acoustic waves with a moving laminar flow, rather than the stationary flow considered in the previously reported numerical studies. 27,28 As mentioned previously, the appropriate modeling of the background flow is essential to study the aforementioned practical applications of a sharp-edge-based micromixer such as sputum liquefaction 30 and chemical gradient generation. 29 To the best of our knowledge, the interaction of a background flow with the acoustic streaming flow has never been investigated previously for a sharp-edge based device.…”
Section: Introductionmentioning
confidence: 99%